2006
DOI: 10.1161/circulationaha.105.595660
|View full text |Cite
|
Sign up to set email alerts
|

Routine Thrombectomy in Percutaneous Coronary Intervention for Acute ST-Segment–Elevation Myocardial Infarction

Abstract: Background-Distal embolization during primary percutaneous coronary intervention (PCI) for ST-elevation myocardial infarction may result in reduced myocardial perfusion, infarct extension, and impaired prognosis. Methods and Results-In a prospective randomized trial, we studied the effect of routine thrombectomy in 215 patients with ST-segment-elevation myocardial infarction lasting Ͻ12 hours undergoing primary PCI. Patients were randomized to thrombectomy pretreatment or standard PCI. The primary end point wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
177
3
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(187 citation statements)
references
References 43 publications
2
177
3
5
Order By: Relevance
“…Various thrombectomy devices have been developed allowing manual or mechanical removal of intracoronary thrombi. All thrombectomy devices have shown benefits compared with conventional PPCI, when surrogate endpoints, such as angiographic flow assessment, LVEF assessment, infarct size reduction by perfusion imaging, enzymatic analysis and ST-segment resolution were used [26,29,[73][74][75][76][77][78][79] . To date evidences about hard endpoints from randomized controlled trials, comparing manual and mechanical thrombectomy, are limited and even conflicting.…”
Section: Thrombectomy Devicesmentioning
confidence: 99%
“…Various thrombectomy devices have been developed allowing manual or mechanical removal of intracoronary thrombi. All thrombectomy devices have shown benefits compared with conventional PPCI, when surrogate endpoints, such as angiographic flow assessment, LVEF assessment, infarct size reduction by perfusion imaging, enzymatic analysis and ST-segment resolution were used [26,29,[73][74][75][76][77][78][79] . To date evidences about hard endpoints from randomized controlled trials, comparing manual and mechanical thrombectomy, are limited and even conflicting.…”
Section: Thrombectomy Devicesmentioning
confidence: 99%
“…In this regard, the use of a mechanical device for thrombus removal or trapping to improve clinical outcomes after p-PCI is attractive, and the efficacy of these devices has been tested in many clinical trials. Although some data, especially those regarding the use of distal protection devices, have failed to show clinical benefits due in part to patient and device selection [48][49][50][51][52][53] , many recent large-scale randomized trials have demonstrated significant improvements in myocardial perfusion 45,[54][55][56][57][58][59][60][61][62][63][64][65][66][67] and the left ventricular function 64,65) in addition to reduced mortality 68) ( 69) . In addition, Burzotta et 70) .…”
Section: Thrombus Aspiration/distal Protection Therapy and Its Efficacymentioning
confidence: 99%
“…[59][60][61] However, it is not clear whether these benefits also lead to smaller infarcts or better clinical outcomes. [62][63][64] Distal embolic protection failed to show improved microvascular flow, greater reperfusion success, reduced infarct size or enhanced event-free survival. 65,66 Prevention and treatment of susceptibility of microcirculation to injury Individual susceptibility of the microcirculation to ischaemia-reperfusion injury is determined by genetic factors, 67 although acquired risk factors (such as diabetes 68 and hypercholesterolaemia 69 ) may modulate its occurrence.…”
Section: Prevention and Treatment Of Distal Embolizationmentioning
confidence: 99%